2014
DOI: 10.4067/s0718-915x2014000300002
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an integrated management system into a small building company

Abstract: Manuscript Code: 0542 Date of reception/acceptation: 15oct2014/01dec2014 ResumenLas empresas de construcción suelen adoptar nuevas herramientas y prácticas de gestión a fin de obtener un mayor nivel de calidad. La integración entre la gestión de la producción y otros sistemas de gestión es importante para el logro de mejoras en la construcción. Sin embargo, en algunos casos, las empresas utilizan estos sistemas de manera aislada y además hay pocos estudios que describen aplicaciones de sistemas integrados en p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The development of an IMS was focused as a research topic by several authors adopting case studies as research methods and addressing companies operating in disparate activity sectors such as those conducted by Brendler and Brandli (2011) in an apparel company, Giacomello et al (2014) and Masood et al (2014) in building companies, Rotaru et al (2005) in the food industry, Lobonţ and Pascu (2012) in higher education institutions, Marques et al (2014) in a waste treatment facility, Mehrabi et al (2013) in a power management company, Satolo et al (2013) in a Brazilian sugar and ethanol manufacturing unit, Walker and McAleer (2014) in a council’s waste management service, von Ahsen (2014) in the automotive industry, López-Fresno (2010) in the airline industry, Khanna et al (2010) in Indian organizations, Bernardo et al (2016) in Greek companies and Vitoreli and Carpinetti (2013) in multiple companies. Amid the studied features, the main motivations (Domingues et al , 2011a, 2014; Simon et al , 2012), drawbacks (Domingues et al , 2012, 2014; Simon et al , 2014b), expected benefits (Bernardo et al , 2015; Carvalho et al , 2015; Zeng et al , 2011), critical success factors (Domingues et al , 2011b; Sampaio et al , 2012), the integration strategies (Bernardo et al , 2011; Ivanova et al , 2014; Karapetrovic, 2002), the integration levels (Abad et al , 2014; Jørgensen et al , 2006), models (Bernardo, 2014; El Idrissi et al , 2014; Olaru, Maier, Nicoarǎ and Maier, 2014; Rebelo et al , 2014) and the extension to other sector specific requirements (Roessler et al , 2014) were widely reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of an IMS was focused as a research topic by several authors adopting case studies as research methods and addressing companies operating in disparate activity sectors such as those conducted by Brendler and Brandli (2011) in an apparel company, Giacomello et al (2014) and Masood et al (2014) in building companies, Rotaru et al (2005) in the food industry, Lobonţ and Pascu (2012) in higher education institutions, Marques et al (2014) in a waste treatment facility, Mehrabi et al (2013) in a power management company, Satolo et al (2013) in a Brazilian sugar and ethanol manufacturing unit, Walker and McAleer (2014) in a council’s waste management service, von Ahsen (2014) in the automotive industry, López-Fresno (2010) in the airline industry, Khanna et al (2010) in Indian organizations, Bernardo et al (2016) in Greek companies and Vitoreli and Carpinetti (2013) in multiple companies. Amid the studied features, the main motivations (Domingues et al , 2011a, 2014; Simon et al , 2012), drawbacks (Domingues et al , 2012, 2014; Simon et al , 2014b), expected benefits (Bernardo et al , 2015; Carvalho et al , 2015; Zeng et al , 2011), critical success factors (Domingues et al , 2011b; Sampaio et al , 2012), the integration strategies (Bernardo et al , 2011; Ivanova et al , 2014; Karapetrovic, 2002), the integration levels (Abad et al , 2014; Jørgensen et al , 2006), models (Bernardo, 2014; El Idrissi et al , 2014; Olaru, Maier, Nicoarǎ and Maier, 2014; Rebelo et al , 2014) and the extension to other sector specific requirements (Roessler et al , 2014) were widely reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The WPC system proposed is to be implemented together with the PCP in the practical application of small and medium-sized companies' construction works. Similar to Giacomello et al (2014) …”
Section: Proposal and Testing Of The Waste Planning And Control Systementioning
confidence: 96%
“…Management systems frequently work in isolation. Giacomello et al (2014) have proposed integrating systems that plan and control production (PCP) with quality, health, and safety in the workplace and with environmental management systems. What is needed is a management system for waste planning and control that can work together with these management systems.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Canadá [22] Colombia [23] [3] Brasil [24], [25], [26], [27], [28], [ [43], [44] India [40], [41] [45], [46], [47], [48], [49], [50] Fuente: elaboración propia.…”
Section: Américamentioning
confidence: 99%